The Advantages and Disadvantages of Conflict at Work - Review, MIT (MIT Sloan Management Review, 2018)
Conflict can be a source of creativity and new ideas, or a weight that drags down people's emotions and productivity. This collection of articles from MIT Sloan Management Review looks at how to deal with strong emotions in the workplace, how to manage divergent points of view, and how to make sure that the company doesn't fall victim to the "Immutable Law of the Ex."